EKSISTENSI DAN URGENSI SOSIOLOGI OLAHRAGA SEBAGAI DISIPLIN ILMU INTEGRATIF DALAM ILMU KEOLAHRAGAAN - Muhammad Arsyad Islam; Ahmad Jibril; Ryan Valentino Purba; Aji Alfattah; Nova Sari Munthe; Riska Mulya; Muhammad Arrival Mahindra; Tipan Fradous Sihombing; Yan Indra Siregar; Putra Arima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sports sociology is a branch of science that examines the relationship between sports activities and social life in society. In the development of modern sports science, sports sociology has an important position because it is able to integrate various disciplines such as education, psychology, culture, economics, and politics in understanding sports phenomena comprehensively. This study aims to analyze the existence and urgency of sports sociology as an integrative discipline in sports science. The research method used is a literature study with a qualitative descriptive approach through the examination of scientific journals, books, and relevant academic sources. The results of the study indicate that sports sociology has a strategic role in understanding various social phenomena in sports, such as character building, social interaction, group solidarity, gender discrimination, sports globalization, and the commercialization of modern sports. In addition, sociological approaches in sports also contribute to the development of sports education and athlete coaching through understanding social and cultural factors that influence sports achievement. Therefore, sports sociology becomes a very important discipline in supporting the development of sports science that is oriented not only toward physical performance and achievement, but also toward social, cultural, and humanitarian values.